P378 Rectal bleeding and stool frequency improvement with tofacitinib dose escalation to, 10 mg BID in patients with Ulcerative Colitis following loss of response on tofacitinib, 5 mg BID maintenance therapy: Results from OCTAVE Open. (21st January 2022) - Allegretti, J R; Gecse, K B; Chiorean, M V; Argollo, M; Guo, X; Lawendy, N; Su, C; Mundayat, R; Paulissen, J; Salese, L; Irving, P M
Abstract: Background: Tofacitinib is an oral, small molecule JAK inhibitor for the treatment of ulcerative colitis (UC). In the tofacitinib UC clinical programme, patients who responded to tofacitinib, 10 mg BID during induction, and experienced treatment failure whilst receiving tofacitinib, 5 mg BID during maintenance (OCTAVE Sustain) and subsequently received tofacitinib, 10 mg BID in the open-label, long-term extension (OLE) study (OCTAVE Open; NCT01470612), comprised the dose escalation subpopulation. The efficacy and safety of tofacitinib in the dose escalation subpopulation have been previously reported. 1 Here, we evaluated patient-reported outcomes to assess rectal bleeding and stool frequency improvement in the dose escalation subpopulation in OCTAVE Open. Methods: The following efficacy endpoints based on the Mayo subscores were analysed in the overall dose escalation subpopulation and by prior tumour necrosis factor inhibitor (TNFi) failure status: rectal bleeding improvement (≥1 point decrease in rectal bleeding subscore [RBS] from OLE study baseline) and stool frequency improvement (≥1 point decrease in stool frequency subscore [SFS] from OLE study baseline), up to Month (M)6 in the OLE study (full analysis set, non-responder imputation). Changes from baseline in partial Mayo score (PMS), RBS and SFS at M1, by M2 clinical response status, were also analysed (as observed). Results: In OCTAVE Open, 57 patients were included in the dose escalation subpopulation, of which, 28 (49.1%) had prior TNFi failure. Overall, at M1 and M6, of OCTAVE Open, 59.6% and, 66.7% of patients had rectal bleeding improvement, respectively (Figure, 1). Corresponding values for stool frequency improvement were, 50.9% and, 64.9%. At most time points, rates of rectal bleeding and stool frequency improvements were similar in patients with and without prior TNFi failure. Patients with a clinical response at M2 had a numerically greater mean decrease from baseline in PMS, RBS and SFS at M1 than those without (Figure 2). Conclusion: In this post hoc analysis, in patients with UC who had loss of response after, 8–52 weeks of treatment with tofacitinib, 5 mg BID (following reduction from induction tofacitinib, 10 mg BID), dose escalation back to, 10 mg BID generally resulted in rectal bleeding and stool frequency improvement in the majority of patients by M1, which was maintained to M6, regardless of prior TNFi failure status. Furthermore, early improvement in RBS and/or SFS at M1 may indicate likelihood of recapturing response at M2 with dose escalation from tofacitinib, 5 to, 10 mg BID. Reference: 1. Sands BE et al. Aliment Pharmacol Ther, 2020;, 51:, 271–280.